Implementation of the prototyping method in the development of information systems (case study: pelangi laundry) - Ade Ragil Bintoro; R. Arri Widyanto; Dimas Sasongko (Borobudur Informatics Review, 2022)
Laundry Pelangi is an individual company engaged in laundry services. Laundry Pelangi is located in Rejosari RT 01 RW 09 Mungkid, Magelang Regency. Currently, Laundry Pelangi's transaction notes and income reports are still done manually using paper-based notes. The manual process has many shortcomings, including inaccurate recording or missing records. This research will develop a laundry information system to help make it easier for employees to manage data and function to create a service feature in the form of free laundry. The method used in the development of this system is the prototyping method, namely identifying user needs, making prototypes, testing prototypes, improving prototypes, developing production versions. Through the development of this system, the transaction ordering process and income report data can be stored properly. The results of the overall test conducted by consumers, employees, and owners obtained a value of 92.11%, which means it is very feasible. It is concluded that the system built can make it easier for employees to process input transactions, print notes and print consumer cards, while consumers make it easier to order laundry and monitor laundry status.